Digital Innovation in Culinary Tourism Services at Galeri Indonesia Kaya, Jakarta - Regita Giri Karuna; Vishnuvardhana S. Soeprapto (Publikasi Indonesia, 2024)
This research discusses implementing innovative digital technology at Galeri Indonesia Kaya, Jakarta, which combines cultural richness with modern concepts. Using a qualitative approach and case studies, this research aims to understand this phenomenon in-depth. Data analysis is done inductively to identify patterns, themes, and relationships among various aspects emerging from the collected data. The results show that the use of digital technology in the food and beverage segment of tourism services at Galeri Indonesia Kaya has had a significant positive impact. This technology improves operational efficiency, service quality, and provides a more personalised experience for visitors. Visitors' response to informative and interactive digital menus is also very positive. In conclusion, the use of digital technology in tourism services at Galeri Indonesia Kaya has brought significant positive impacts, improving operational efficiency, service quality, and visitor experiences on a personal level.